2003
DOI: 10.1038/sj.npp.1300327
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Risperidone, Olanzapine, and Haloperidol in Psychotic Youth: A Double-Blind, Randomized, 8-Week Trial

Abstract: This pilot study was undertaken to estimate the acute antipsychotic effect size and side effect propensity of risperidone and olanzapine in the pediatric population, in comparison to haloperidol, a conventional antipsychotic with established efficacy. Risperidone and olanzapine are widely used as first-line treatments to ameliorate psychotic symptoms in youth, but their abilities to specifically treat children and adolescents presenting due to psychotic symptoms have not been rigorously studied. Subjects, sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
150
4
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(173 citation statements)
references
References 37 publications
15
150
4
4
Order By: Relevance
“…In a previous 8-week doubleblind, randomized, controlled trial in 50 children and adolescents with psychotic symptoms, comparing risperidone, olanzapine, and haloperidol, there was no difference in efficacy among the drugs, with all three antipsychotics providing a significant reduction in psychotic symptoms [38]. More recently, a 12-week open-label, randomized study comparing risperidone and olanzapine efficacy in 25 child-onset schizophrenia patients reported that both drugs provided a similar significant reduction in psychotic symptoms [28].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In a previous 8-week doubleblind, randomized, controlled trial in 50 children and adolescents with psychotic symptoms, comparing risperidone, olanzapine, and haloperidol, there was no difference in efficacy among the drugs, with all three antipsychotics providing a significant reduction in psychotic symptoms [38]. More recently, a 12-week open-label, randomized study comparing risperidone and olanzapine efficacy in 25 child-onset schizophrenia patients reported that both drugs provided a similar significant reduction in psychotic symptoms [28].…”
Section: Discussionmentioning
confidence: 90%
“…In a more recent study, clozapine was significantly superior to olanzapine only for the treatment of negative symptoms [37]. In the only other double-blind randomized study, Sikich et al [38] studied 50 patients with psychotic symptoms, with a mean length of illness of 2.4 years. Haloperidol, olanzapine, and risperidone showed similar efficacy in symptom reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, however, an insignificant decrease was reported in HDL levels after 8 weeks in patients treated with olanzapine, while a very small increase was determined in patients treated with risperidone. Low-density lipoprotein and triglyceride levels were reported to increase in both groups [35]. In contrast to these findings, another study involving a different patient group observed a small increase in HDL levels in patients receiving olanzapine after 8 weeks' treatment, while a decrease was observed in HDL levels in patients treated with risperidone [36].…”
Section: Discussionmentioning
confidence: 87%
“…Unfortunately, adverse effects were not reported, making evaluation of the risk-benefit ratio difficult. However, clinical trials using risperidone in psychotic adolescents suggest that risperidone treatment is likely to be associated with weight gain, as well as neurologic and other side effects [43].…”
Section: Early Identification and Interventionmentioning
confidence: 99%